Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
I'm not sure if the answer is right, but here you go.
y=mx+b
'm' is for gradient of the line. First, calculate the gradient.
Let's use (6,15) and (8,21)
Gradient, m = [tex]y_{2} [/tex] - [tex] y_{1} [/tex]
--------------
[tex] x_{2} [/tex] - [tex] x_{1} [/tex]
= 21 - 15 = 6 = 3
----------- ----
8 - 6 2
Therefore, m = 3 . Now let's search 'b' .
Let's use (6,15) again. Substitute it into the equation.
y=mx+b
15 = 3 (6) + b
b = -3
Thus, the equation : y=3x -3
y=mx+b
'm' is for gradient of the line. First, calculate the gradient.
Let's use (6,15) and (8,21)
Gradient, m = [tex]y_{2} [/tex] - [tex] y_{1} [/tex]
--------------
[tex] x_{2} [/tex] - [tex] x_{1} [/tex]
= 21 - 15 = 6 = 3
----------- ----
8 - 6 2
Therefore, m = 3 . Now let's search 'b' .
Let's use (6,15) again. Substitute it into the equation.
y=mx+b
15 = 3 (6) + b
b = -3
Thus, the equation : y=3x -3
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.